Metabolic and Bactericidal Effects of Targeted Suppression of NadD and NadE Enzymes in Mycobacteria - Irina A. Rodionova (American Society for Microbiology, 2014)
ABSTRACT Mycobacterium tuberculosis remains a major cause of death due to the lack of treatment accessibility, HIV coinfection, and drug resistance. Development of new drugs targeting previously unexplored pathways is essential to shorten treatment time and eliminate persistent M. tuberculosis. A promising biochemical pathway which may be targeted to kill both replicating and nonreplicating M. tuberculosis is the biosynthesis of NAD(H), an essential cofactor in multiple reactions crucial for respiration, redox balance, and biosynthesis of major building blocks. NaMN adenylyltransferase (NadD) and NAD synthetase (NadE), the key enzymes of NAD biosynthesis, were selected as promising candidate drug targets for M. tuberculosis. Here we report for the first time kinetic characterization of the recombinant purified NadD enzyme, setting the stage for its structural analysis and inhibitor development. A protein knockdown approach was applied to validate bothNadD and NadE as target enzymes. Induced degradation of either target enzyme showed a strong bactericidal effect which coincided with anticipated changes in relative levels of NaMN and NaAD intermediates (substrates of NadD and NadE, respectively) and ultimate depletion of the NAD(H) pool. A metabolic catastrophe predicted as a likely result of NAD(H) deprivation of cellular metabolism was confirmed by 13C biosynthetic labeling followed by gas chromatography-mass spectrometry (GC-MS) analysis. A sharp suppression of metabolic flux was observed in multiple NAD(P)(H)-dependent pathways, including synthesis of many amino acids (serine, proline, aromatic amino acids) and fatty acids. Overall, these results provide strong validation of the essential NAD biosynthetic enzymes, NadD and NadE, as antimycobacterial drug targets. IMPORTANCE To address the problems of M. tuberculosis drug resistance and persistence of tuberculosis, new classes of drug targets need to be explored. The biogenesis of NAD cofactors was selected for target validation because of their indispensable role in driving hundreds of biochemical transformations. We hypothesized that the disruption of NAD production in the cell via genetic suppression of the essential enzymes (NadD and NadE) involved in the last two steps of NAD biogenesis would lead to cell death, even under dormancy conditions. In this study, we confirmed the hypothesis using a protein knockdown approach in the model system of Mycobacterium smegmatis. We showed that induced proteolytic degradation of either target enzyme leads to depletion of the NAD cofactor pool, which suppresses metabolic flux through numerous NAD(P)-dependent pathways of central metabolism of carbon and energy production. Remarkably, bactericidal effect was observed even for nondividing bacteria cultivated under carbon starvation conditions.